認知症有病者の遺族および診療やケアに携わる医療者自身が認知症になった場合に希望する死亡場所とその関連要因：インターネット調査 - 林 ゑり子; 山田 藍; 青山 真帆; 升川 研人; 宮下 光令 (日本看護科学会誌, 2023)
要旨　目的：認知症有病者を看取った遺族と認知症のケアの経験がある医療職を対象者として，自分が認知症になった際の希望の死亡場所とその関連要因を明らかにする．　方法：横断的デザインによるインターネット調査を2019年10月に実施した．対象者は，認知症有病者の遺族（n＝618），医師（n＝198），看護職（n＝197），介護職（n＝193）とした．　結果：認知症有病者の遺族の希望の死亡場所は，自宅が33％，病院が31％，介護施設が32％であった．医療者は，遺族に比べ自宅の割合が41％〜51％と高く，病院の割合が15〜20％と低かった（P＜.001）．遺族の希望の死亡場所は故人の死亡場所と関連していた（故人の死亡場所が介護施設；OR＝2.80，P＜.001，自宅；OR＝1.58，P＝.05）．　考察：認知症有病者を看取った遺族は，看取りを経験した自宅や介護施設において遺族の経験を通して得た，満足感や看取った場所のイメージが影響している．もしくは，自らが望ましいと考えている死亡場所で遺族の看取りを行った可能性がある． 　Objective: The aim of this study is to clarify the preferred place of death and related factors when dementia occurs, targeting the bereaved families of dementia patients and medical professionals.　Methods: Cross-sectional internet survey was conducted in October 2019. The subjects were the bereaved family (n＝618), doctors (n＝198), nurses (n＝197), and care workers (n＝193).　Results: The preferred place of death for the bereaved families were homes (33％), hospitals (31％), and care facilities (32％). In addition, the proportion of medical professionals at home tended to be 41％-51％ higher than that of bereaved families. The desired place of death of the bereaved family was related to the deceased's place of death (Nursing care home; OR＝2.80, P＜.001, Home; OR＝1.58, P＝.05).　Conclusion: The bereaved families who took care of dementia patients experienced good care at home and nursing homes. It was suggested that the desired place of the bereaved family may be related to the image obtained through the experience of the bereaved family.